Konsep Toleransi Beragama pada Remaja Suku Bugis Makassar - Novina Sabila Zahra; Andi Ramdhan Al-Qadri (Jurnal Psikologi Islam dan Budaya, 2022)
This study aims to explore the concept of religious tolerance in Bugis Makassar youth. This research is a construct realism qualitative research with an indigenous psychology approach. Indigenous psychology approach is used to explore individual understanding of a concept, especially the concept of tolerance which is inseparable from cultural and social influences. The respondents were 130 teenagers with the age ranged from 18 to 21 years old, and were asked to fill an open-ended questionnaire.. The results showed that religious tolerance was interpreted by Bugis Makassar youth as feelings and respect for other religions. The attitude towards others with different religion was indicated by feeling happy or okay and not having problem with different religion. The expression of religious tolerance was did not disturb others in doing their worships. Also, the response of the situation involving other religions' activities were welcoming and respecting other religions' activities. This finding indicated that individuals with religious tolerance are those who can respect and accept other religions in their surrounding environment.